Pnioki, krzoki i ptoki… projekty tożsamościowe liderów organizacji śląskich - Ewa Michna, Ewa Michna (Człowiek i Społeczeństwo, 2017)
Ethnic leaders play an increasingly important role in shaping the ethnic ties and functioning of ethnic groups. National and ethnic elites are also advocates of collective identity. They create the criteria of ethnic identity and develop identity constructs. Such constructs are to be the frame for the creation of the individual identity of the members of the group. While formulating identity projects leaders must be in dialogue with the group which they wish to influence. In this paper, I will show the complexity of these processes. In the eighty narratives collected during my research on Silesian ethnic leaders we see individual ways of constructing identity and boundaries of group practices of everyday life (where identity is negotiated and multiple, based on the symbolic resources and categorizations available in the group – the pnioki, krzoki and ptokiof the title), and, on the other hand, identity projects constructed in a more conscious way. The latter are created in the context of identity politics, which my interlocutors lead on behalf of the collective entity (in this case, the Silesian community).